Elevated tropospheric ozone and crop production: potential negative effects and plant defense mechanisms - Nowroz, Farzana; Hasanuzzaman, Mirza; Siddika, Ayesha; Parvin, Khursheda; Caparros, Pedro Garcia; Nahar, Kamrun; Prasad, P.V. Vara (Frontiers in Plant Science, 2024)
Ozone (O3) levels on Earth are increasing because of anthropogenic activities and natural processes. Ozone enters plants through the leaves, leading to the overgeneration of reactive oxygen species (ROS) in the mesophyll and guard cell walls. ROS can damage chloroplast ultrastructure and block photosynthetic electron transport. Ozone can lead to stomatal closure and alter stomatal conductance, thereby hindering carbon dioxide (CO2) fixation. Ozone-induced leaf chlorosis is common. All of these factors lead to a reduction in photosynthesis under O3 stress. Long-term exposure to high concentrations of O3 disrupts plant physiological processes, including water and nutrient uptake, respiration, and translocation of assimilates and metabolites. As a result, plant growth and reproductive performance are negatively affected. Thus, reduction in crop yield and deterioration of crop quality are the greatest effects of O3 stress on plants. Increased rates of hydrogen peroxide accumulation, lipid peroxidation, and ion leakage are the common indicators of oxidative damage in plants exposed to O3 stress. O3 disrupts the antioxidant defense system of plants by disturbing enzymatic activity and non-enzymatic antioxidant content. Improving photosynthetic pathways, various physiological processes, antioxidant defense, and phytohormone regulation, which can be achieved through various approaches, have been reported as vital strategies for improving O3 stress tolerance in plants. In plants, O3 stress can be mitigated in several ways. However, improvements in crop management practices, CO2 fertilization, using chemical elicitors, nutrient management, and the selection of tolerant crop varieties have been documented to mitigate O3 stress in different plant species. In this review, the responses of O3-exposed plants are summarized, and different mitigation strategies to decrease O3 stress-induced damage and crop losses are discussed. Further research should be conducted to determine methods to mitigate crop loss, enhance plant antioxidant defenses, modify physiological characteristics, and apply protectants.